Peptides from Amaranth controlled the NF-κB pathway activation on epithelial cells and suppressed intestinal inflammation - Smaldini, Paola (2018)
Biological, nutritional and health benefits of amaranth have been highlighted in the last years. Proteins of amaranth exert anti-hypertensive, anti-oxidant, anti-thrombotic and anti-proliferative effects. The aim of this study was to analyze the anti-inflammatory effect of peptides from amaranth on NF-kB-intracellular pathway activation in intestinal epithelial cells, and in experimental intestinal inflammation, such as colitis and food allergy. Colon cell lines (Caco-2 and Caco-luc) were cultured with flagellin and amaranth peptides. CCL20-expression was evaluated by qPCR and NF-κB modulation was evaluated by light emission and qPCR, along with p65-nuclear traslocation. In vivo studies included the oral administration of a formulation containing the peptide during the allergic sensitization or the colitis induction phase in Balb/c mice. Treatment efficacy was in vivo and in vitro evaluated. We found several peptides with anti-inflammatory capacity and we selected that with the highest ability to suppress cell activation (decrease in CCL20 and light emission p<0.05). In vivo studies showed, an amelioration of the clinical score (p<0.01) in the food allergy mouse model, with inhibition of specific-IgE secretion (p<0.05) and negativitization of the cutaneous test (mean increase in footpad thickness control: 0.6mm vs peptide-treated: 0.3mm; p<0.05); intestinal nf-kb gene expression was reduced (fold change=3; p<0.01) along with up-regulation of tfg-b and foxp3. In the colitis mouse model, we found a decrease of the histologic score with a decrease expression and production of pro-inflammatory cytokines (IL-1b, TNF and IFNg, p<0.05) and a decrease in the myeloperoxidase activity in the peptide-treated group compared to control (p<0.05). NF-κB pathway was also abrogated in the gut. In conclusion, our findings indicated that peptides from amaranth endowed mucosal anti-inflammatory properties that suppressed the intestinal activation of NF-kB in Th1- and Th2-mediated inflammation. These findings led us to propose that this peptide might be included in the composition of a functional food